Land use and trip production model in central and peri-urban Semarang to anticipate land use conversion in post pandemic era. Issue 1 (1st September 2022) - Basuki, Y; Rahayu, S
Abstract: The development of core and peri-urban Semarang has land use conversion that increases human mobility. If this phenomenon is not well anticipated, it will cause transportation problems such as inefficiency of energy, and pollution. After the pandemic, the urban activity will be normal, and land use conversion will be more extensive again. A transportation model is needed to understand the land use that most influences the movement. This article aims to formulate a mathematical model that can identify land uses that affect trips or movement. To build a model, data on trip production in each village in core and peri-urban Semarang as the dependent variable and the various land use as independent variables. The regression model obtained by D = 0.009 residence + 1432.529 with R2 0.597. in the core of Semarang and D = 0.004 residence – 991.223 with R2 0.791 in peri-urban. The results of this model show that the most influential type in causing trip attraction is residential land use both in peri-urban and in core Semarang with a different coefficient. According to these findings, it requires more attention from the Semarang City Government to regulate land use in anticipation of transportation problems.